Perception de l’ambiance sonore d’un lieu selon sa représentation visuelle : une analyse de corpus - Laura Ascone; Catherine Dominguès; Julien Longhi (Corela)
This study investigates the way the visual representation of a place influences its acoustic atmosphere’s perception and description. This analysis is based on a survey aiming at contrasting four different representations (supports): a captioned map, an ortophoto, a collection of pictures, and a map accompanied by pictures. The answers were transcribed and constituted four sub-corpus (one per support) on which a discursive analysis was conducted. Different semantic categories were established. They refer to the spotting of visual elements, the inferences between these visual elements and the acoustic atmosphere, and the speaker’s subjectivity. A statistical analysis of the words constituting these categories was conducted in order to contrast the use of the categories according to the support. This analysis revealed that this use depends on the support and that the acoustic atmosphere’s description and perception vary according to the visual representation.